Evaluasi Fisik Sediaan Krim Tabir Surya dari Bubur Rumput Laut Kappaphycus alvarezii dan Turbinaria conoides - Rini Yanuarti; Nurjanah Nurjanah; Effionora Anwar; Ginanjar Pratama (Jurnal FishtecH, 2021)
Seaweed is one of the aquatic commodities which has many bioactive compounds. This bioactive compound is widely used in the cosmetic industry. In the cosmetic industry, usually has only one species of seaweed was used. The use of a combination of two seaweeds has not been widely used, therefore this study aims to determine the best sunscreen cream from the physical evaluation results of Kappaphycus alvarezii and Turbinaria conoides. The stages in this study were the making of seaweed porridge, formulation of sunscreen cream, and physical evaluation which included homogeneity, consistency of cream, cycling test, and organoleptic. In the homogeneity observation and cycling test, it was found that all treatments (cream concentration 0%, 10%, 20%, and 30%) had homogeneous and stable properties. The best cream consistency results were found in cream with 30% concentration (370x10–1). In organoleptic observations (appearance, color, and aroma) all creams with the addition of seaweed (cream concentration 10%, 20%, and 30%) were not significantly different. However, when compared to cream with 0% concentration, the results were significantly different. In this study, the sunscreen cream with the addition of 30% concentration of the combination of K. alvarezii and T. conoides is the best cream.